Strengthening Of Kenahdlatululamaan Learning In Educational Institutions - Yusnaili Budianti; Mohammad Al Farabi; Ilham Amara Malik Daulay (Institut Agama Islam An-Nawawi Purworejo, 2022)
This research is a form of qualitative research. Implement this research to observe or examine the strengthening of kenahdlatul ulamaan learning in Islamic boarding schools and nahdliyin schools in Medan City. The results of the study show that: The planning of educational institutions in implementing nahdlatululamaan learning at Islamic boarding schools and Nahdliyin schools in Medan City starts from the preparation of lesson plans for the Aswajaan subject carried out based on reference to the Local Content of Aswajaan subjects, Implementation of nahdlatululamaan learning in Nahdliyin Schools and Islamic Boarding Schools in Medan City such as : intra-curricular and extra-curricular activities that support the development of the moral character of the santri, as well as applying moderate values ​​in various activities. 3) Evaluations are carried out such as: testing and paying attention to students' religious habits by practicing ahlussunnah wal Jamaah, as well as other activities to improve the quality of kenahdlatululamaan.